Clinical-Immunologic Basis of using Vitaminous-Mineral Complex and Imunophan in Rehabilitation for Patients with Hemorrhagic Fever with Renal Syndrome - G. M. Khasanova; A. V. Tutelyan; D. A. Valishin (Журнал инфектологии)
The efficiency of using Imunophan, Milgamma, Vitrum-antioxidant in a multimodality therapy during a recovery period for patients with hemorrhagic fever with renal syndrome has been studied. Statistically-valid the given therapy leads to the decrease of TNF-α, IL-4, IL-10 level, the increase of INF-γ и IL-2 levels, improves cellular immunity and increases an induction index and working balance of phagocytes. Stabilization of vitamin status was exposed with patients suffering from a middle form of hemorrhagic fever with renal syndrome (HFRS) and significant improvement of a vitamin ratio with patients suffering from a bad form of HFRS. Positive influence on phylaxis , vitamin status, an essentialmicroelement level leads to a clinical improvement of disease state.